Where have all the nurses gone? - Shields, Linda; Watson, R. (Australian Nursing Federation, 2008)
The aim of this article is to highlight a crisis that has developed in UK nursing. The nursing workforce worldwide is diminishing and the UK nursing workforce is no exception. While steps are being taken in the UK to alleviate the nursing shortage by funding more places in university nursing departments, this initiative is no longer viable due to the financial crisis in the NHS, which funds nursing education. The significant influx of international nurses to the UK is likely to be a short-term solution to a long-term problem as this incipient form of neo-colonialism is seen to deplete developing countries of their nurses, and international nursing bodies condemn it.The outcome of the crisis may well lead to the disappearance of nurses from the UK NHS workforce as they are replaced by the cheaper alternative of health care assistant and technicians. This can only be to the detriment of patients.